Pierres et hommes. - Kérisel, Jean, 1908- author.
1 online resource (128 pages)
Keywords: "Of Stones and Man explores the many errors of judgement made by civilizations both ancient and modern across the world. Arrogance and a penchant for excess drove mankind to build ever greater and more ambitious edifices. The author analyses these works from a scientific and historically-sensitive perspective, highlighting the hydro-geological background to repeated infamous disasters, from the faults inherent in the Sphinx to the leaning Tower of Pisa."--Jacket.